2012
DOI: 10.1002/pi.4342
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization behavior and crystallite morphology control of poly(L‐lactic acid) through N, N′‐bis(benzoyl)sebacic acid dihydrazide

Abstract: Adding a nucleating agent is one of the best ways to accelerate the crystallization rate of poly(L-lactic acid) (PLLA) so as to obtain a high degree of crystallinity during the process, which will improve the heat distortion temperature of final products. In the work reported, N, N -bis(benzoyl)sebacic acid dihydrazide (BSAD) was synthesized and used as a nucleating agent for PLLA. Isothermal and non-isothermal crystallization behaviors were investigated using differential scanning calorimetry (DSC). The addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 49 publications
0
15
0
Order By: Relevance
“…Among these PLLA/APAD samples, PLLA/0.5 %APAD exhibits the highest onset crystallization temperature of 136.4 °C and crystallization peak temperature of 132.0 °C, as well as the largest non-isothermal crystallization enthalpy of 48.1 J/g, indicating that the enhancement of 0.5 wt.% APAD on the crystallization of PLLA is the best. On the other hand, under the same circumstance, the higher onset crystallization temperature and crystallization peak temperature, as well as the larger non-isothermal crystallization enthalpy of PLLA/APAD system further confirm the more powerful accelerating ability of APAD for PLLA crystallization comparing with other systems such as PLLA/BASD [11], PLLA/NA [33], PLLA/MCB [34]. Additionally, with increasing of APAD concentration, the crystallization peak shifts to the lower temperature, and the value of the non-isothermal crystallization enthalpy also becomes smaller.…”
Section: Non-isothermal Crystallizationmentioning
confidence: 72%
See 1 more Smart Citation
“…Among these PLLA/APAD samples, PLLA/0.5 %APAD exhibits the highest onset crystallization temperature of 136.4 °C and crystallization peak temperature of 132.0 °C, as well as the largest non-isothermal crystallization enthalpy of 48.1 J/g, indicating that the enhancement of 0.5 wt.% APAD on the crystallization of PLLA is the best. On the other hand, under the same circumstance, the higher onset crystallization temperature and crystallization peak temperature, as well as the larger non-isothermal crystallization enthalpy of PLLA/APAD system further confirm the more powerful accelerating ability of APAD for PLLA crystallization comparing with other systems such as PLLA/BASD [11], PLLA/NA [33], PLLA/MCB [34]. Additionally, with increasing of APAD concentration, the crystallization peak shifts to the lower temperature, and the value of the non-isothermal crystallization enthalpy also becomes smaller.…”
Section: Non-isothermal Crystallizationmentioning
confidence: 72%
“…However, the glass transition temperature of the amorphous PLLA is about 60 °C [10], which can not meet the using requirements of plastic products including disposable tableware, electronics enclosures and automotive interior parts [11]. For PLLA as a semicrystalline polymer, enhancing the crystallinity of PLLA is one of the most effective way to improve its heat resistance.…”
Section: Introduction mentioning
confidence: 99%
“…Acid Dihydrazide. N,N,N -Tris(benzoyl) trimesic acid dihydrazide (TTAD) was prepared as shown in Scheme 1; the specific reaction process is similar to the other amide compounds reportedin our previous works [12,13].…”
Section: Synthesis Of Nnn -Tris(benzoyl) Trimesicmentioning
confidence: 88%
“…There exist many literatures about PLLA and its composites based on PLLA [2,3], and the addition of a functional additive can significantly improve the properties of PLLA. For example, Fan et al [4] reported that N, N'-bis(benzoyl)sebacic acid dihydrazide was synthesized and used as a nucleating agent for PLLA. The addition of N, N'-bis(benzoyl)sebacic acid dihydrazide enhanced the crystallization rate of PLLA, and thermogravimetric analysis showed that the thermal stability of PLLA with N, N'-bis(benzoyl)sebacic acid dihydrazide was enhanced, indicating that there were strong hydrogen bonds between N, N'-bis(benzoyl)sebacic acid dihydrazide and PLLA matrix.…”
Section: Introductionmentioning
confidence: 99%